The Relationship Of The Role Of Delivery Aid, Breastfeeding Frequency, And Family Support With Exclusive Breastfeeding At Pmb Nurachmi Palembang In 2022 - Sahada Kartini; Fika Minata Wathan; Putu Lusita Nati Indriani; Satra Yunola; Siti Aisyah (Science Midwifery, 2022)
orld Health Organization (WHO) and United Nations of Children's Fund (UNICEF) regarding the global strategy for infant breastfeeding stated that the prevention of infant mortality is through proper feeding, ie through exclusive breastfeeding for 6 months and the introduction of complementary foods ( MPASI). This study aims to determine the correlation of the roles of the childbirth helper, breastfeeding frequency and family support at PMB Nurachmi Palembang in 2022. Analytical Survey was used as the research design with a Cross Sectional approach. The sampling technique in this study was carried out by accidental sampling with a total sample of 45 respondents. Data collection was done through a questionnaire sheet and data analysis used Univariate analysis and bivariate analysis using Chi Square test. The Univariate results showed 22 respondents (48.9%) giving exclusive breastfeeding, while 23 respondents (51.1%) did not give exclusive breastfeeding were. The respondents with the good category for the role of childbirth helpers were at 73.3%, those in the good category for the breastfeeding frequency were at 75.6% and the respondents with the high category of family support were at 51.1%. The results of the Chi Square statistical test showed that there was a role of childbirth helper with exclusive breastfeeding (p value = 0.023; OR = 7.692), there was no correlation of breastfeeding frequency and exclusive breastfeeding (p value = 1,000; OR = 1,200 ) and there was a correlation of family support to exclusive breastfeeding (p value = 0.039; OR = 5.556). Conclusion: there was a correlation of the childbirth helper and family support to the exclusive breastfeeding. It is expected that healthcare personnel are able to provide counseling and information to mothers who have babies regarding exclusive breastfeeding and for families to provide information and support to mothers regarding exclusive breastfeeding.